A TLR7 agonist strengthens T and NK cell function during BRAF‐targeted therapy in a preclinical melanoma model. Issue 5 (4th December 2019) - Bellmann, Lydia; Cappellano, Giuseppe; Schachtl‐Riess, Johanna F.; Prokopi, Anastasia; Seretis, Athanasios; Ortner, Daniela; Tripp, Christoph H.; Brinckerhoff, Constance E.; Mullins, David W.; Stoitzner, Patrizia
Abstract : Therapeutic success of targeted therapy with BRAF inhibitors (BRAFi) for melanoma is limited by resistance development. Observations from preclinical mouse models and recent insights into the immunological effects caused by BRAFi give promise for future development of combination therapy for human melanoma. In our study, we used the transplantable D4M melanoma mouse model with the BRAF V600E mutation and concomitant PTEN loss in order to characterize alterations in tumor‐infiltrating effector immune cells when tumors become resistant to BRAFi. We found that BRAFi‐sensitive tumors displayed a pronounced inflammatory milieu characterized by high levels of cytokines and chemokines accompanied by an infiltration of T and NK cells. The tumor‐infiltrating effector cells were activated and produced high levels of IFN‐γ, TNF‐α and granzyme B. When tumors became resistant and progressively grew, they reverted to a low immunogenic state similar to untreated tumors as reflected by low mRNA levels of proinflammatory cytokines and chemokines and fewer tumor‐infiltrating T and NK cells. Moreover, these T and NK cells were functionally impaired in comparison to their counterparts in BRAFi‐sensitive tumors. Their effector cell function could be restored by additional peritumoral treatment with the TLR7 agonist imiquimod, a clinically approved agent for nonmelanoma skin cancer. Indeed, resistance to BRAFi therapy was delayed and accompanied by high numbers of activated T and NK cells in tumors. Thus, combining BRAFi with an immune stimulating agent such as a TLR ligand could be a promising alternative approach for the treatment of melanoma. Abstract : What's new? While inhibitors targeting mutant BRAF proteins can induce melanoma regression, many tumors become resistant to these agents, possibly owing to immunological effects of BRAF inhibitor therapy. Here, using a preclinical mouse model, the authors show that during the early treatment phase with BRAF inhibitors, melanomas are highly immunogenic, with infiltrating T cells and natural killer cells. When resistance develops, however, tumors regress toward low immunogenicity, similar to untreated tumors. Experiments show that in the BRAF‐sensitive phase, peritumoral injection of the TLR7 ligand imiquimod preserves immunogenicity and delays resistance, thus representing a potentially effective novel therapeutic strategy for melanoma.